Kimura Disease: A case report and review of literature (Bangladesh Journal of Medical Science, 2018)
Kimura disease is a rare chronic inflammatory disease with angiolymphatic proliferation of unknown etiology predominantly seen among young Asian males. It classically shows a triad of non-tender subcutaneous masses predominantly in head and neck region with tissue and blood eosinophilia and raised serum IgE level. Here we present a case report of a 24 years male with bilateral pre-auricular and post-auricular swelling for 6 years. The diagnosis of Kimura disease was made on the basis of clinical and histopathological examination.Bangladesh Journal of Medical Science Vol.17(1) 2018 p.152-154